Polymorphic transformations of NaYGeO4 olivine under high pressure and high temperature. Issue 4 (15th February 2023) - Melkozerova, Marina A.; Dyachkova, Tatyana V.; Tyutyunnik, Alexander P.; Enyashin, Andrey N.; Chufarov, Alexander Yu.; Baklanova, Yana V.; Zubkov, Vladimir G.
Abstract: Two new high-pressure modifications of sodium yttrium germanate NaYGeO4 are described. A reversible pressure-induced phase transition of olivine-type NaYGeO4 to new phases has been studied in the pressure range of 4–10 GPa at temperatures from 400 to 1000°C. It was shown that NaYGeO4 olivine is stable at 400–600°C up to 10 GPa. A high-pressure polymorph of NaYGeO4 with NaNdSiO4 crystal structure is formed at 800°C starting from 6 GPa. Along with this polymorph, another new high-pressure modification of NaYGeO4 with NaSmSiO4 crystal structure was found in small amount. In addition, a yet undescribed polymorph of Y2 Ge2 O7 with pyrochlore-type structure was isolated at 8 GPa and 800°C. The crystal structures of the new phases were determined by X-ray powder diffraction. The results of DFT calculations confirmed the experimental crystallography and gave a preliminary insight into the relative thermodynamic stability and electronic properties for all three new compounds.